Evaluation of vitamin D bioaccessibility and mineral solubility from test meals containing meat and/or cereals and/or pulses using in vitro digestion. (15th June 2021) - Antoine, Tiffany; Icard-Vernière, Christèle; Scorrano, Giulia; Salhi, Amal; Halimi, Charlotte; Georgé, Stéphane; Carrière, Frédéric; Mouquet-Rivier, Claire; Reboul, Emmanuelle
Highlights: Complex test meals containing vitamin D and minerals were digested in vitro . Complex test meals were made of meat and/or semolina and/or chickpeas. Chickpeas reduced vitamin D and mineral transfer to the aqueous phase during digestion. The presence of meat induced a decrease in vitamin D stability. Our model can be useful to screen micronutrient bioaccessibility from complex test meals. Abstract: In this study, we evaluated vitamin D and mineral (iron, zinc, magnesium) transfer to the bolus aqueous phase during the digestion of meals with/without pulses. We performed in vitro digestions using test meals made either of i) beef and/or semolina and/or chickpeas, or of ii) potatoes supplemented or not with fibers, phytates, tannins and saponins. Chickpea presence led to a decrease in vitamin D bioaccessibility (−56%, p ≤ 0.05) and mineral solubility (−28% for iron, p ≤ 0.05) compared with meals with beef and/or semolina only. This effect was largely compensated for vitamin D by the fact that this vitamin was more stable during digestion of meals based on plant foods only than of meals with beef. Tannins were the most deleterious compounds for iron solubility, while phytates and tannins decreased vitamin D bioaccessibility. Agronomical or technical solutions to selectively decrease the amount in pulses of compounds that affect micronutrient bioavailability should be further explored.